Efficacy and tolerability of ramucirumab monotherapy or in combination with paclitaxel in gastric cancer patients from the Expanded Access Program Cohort by the Korean Cancer Study Group (KCSG) - Jung, Minkyu; Ryu, Min-Hee; Oh, Do Youn; Kang, Myounghee; Zang, Dae Young; Hwang, In Gyu; Lee, Keun-Wook; Kim, Ki Hyang; Shim, Byoung Yong; Song, Eun Kee; Sym, Sun Jin; Han, Hye Sook; et al. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2018)
Background Ramucirumab improves survival in gastric cancer patients. The efficacy and safety of ramucirumab outside of a clinical trial were evaluated using an expanded access program (EAP). Methods Advanced gastric cancer patients treated with ramucirumab in combination with paclitaxel or with ramucirumab monotherapy in a Korean EAP were evaluated. Baseline characteristics were assessed for progression-free survival (PFS) and overall survival (OS), and adverse events were evaluated according to the treatment regimen. Results Of 265 patients, 228 received ramucirumab plus paclitaxel, and 37 received ramucirumab monotherapy. Grade 3 or 4 neutropenia was more common with ramucirumab plus paclitaxel than with ramucirumab monotherapy (46.7 vs. 8.1%). Gastrointestinal (GI) perforation developed in seven patients (3.1%) in the ramucirumab plus paclitaxel group. The overall response and disease control rates were 16.6 and 66.3% in the ramucirumab plus paclitaxel group, and 5.4 and 37.8% in the ramucirumab monotherapy group, respectively. PFS and OS were 3.8 and 8.6 months in the ramucirumab plus paclitaxel group, and 1.8 and 6.4 months in the ramucirumab monotherapy group, respectively. In multivariate analysis, alkaline phosphatase, albumin, and neutrophil-to-lymphocyte ratio (NLR) were the independent prognostic factors for PFS, while albumin, NLR, number of metastatic sites, and large amount of ascites were independent prognostic factors for OS. Conclusion In the Korean EAP cohort, ramucirumab showed similar efficacy to the results of the previous trials for gastric cancer. However, the level of GI perforation was slightly increased in the ramucirumab plus paclitaxel group.